Nightshift Rotation Schedule and Fatigue in U.K. and Italian Nurses - Lecca, Rosamaria; Westwell, Alison; Casaglia, Elisa; Figorilli, Michela; Murphy, Elizabeth; Puligheddu, Monica; Van Tongeren, Martie; Cocco, Pierluigi (La Medicina del Lavoro, 2024)
Background: Whether hours on shift might impact adaptation to night shift work is still controversial. Methods: We conducted a pooled analysis of two studies, including 170 hospital nurses working night shifts, 116 from a United Kingdom study working 12-hour rotating shifts, and 54 from Italy working 8-hour shifts. Both studies used the Epworth Sleepiness Scale (ESS) to detect sleepiness during routine daytime activities as an indicator of fatigue. We compared the prevalence of daytime sleepiness, as indicated by an ESS score≥11, resulting from either shift work schedule. We used logistic regression to calculate the risk of daytime sleepiness associated with 12-hour vs. 8-hour nightshifts, adjusting by age, sex, and parenting children aged≤4. Results: When comparing similar work circumstances, nightshifts prolonged to 12 hours did not increase the risk of daytime sleepiness compared to 8 hours (OR=0.9, 95% CI 0.32, 2.59). Conclusions: Our results suggest that 12-hour rotating nightshifts with additional rest days and 8-hour rotating shift schedules do not differ in their impact on daytime sleepiness. Further research is warranted on what strategies might effectively contrast fatigue, circadian misalignment, and the related metabolic changes leading to adverse health outcomes, including cancer.